ESC-leitlinienbasierte Therapieempfehlungen für herzinsuffiziente Patienten in der Herzchirurgie - Heim, Christian; Tandler, Rene; Weyand, Michael (Zeitschrift für Herz-, Thorax- und Gefäßchirurgie, 2018)
Background: Heart failure is a common and potentially fatal condition with increasing numbers of patients suffering from chronic heart failure. Current national and European guidelines include surgical options for the treatment of congestive heart failure. Objective: The aim of this article is to provide physicians actively involved in cardiac surgery with a practice-related overview of guideline-based treatment approaches for heart insufficiency. Material and methods: The current guidelines of the European Society of Cardiology (ESC) were utilized as the foundations of this review article and those topics which are relevant for cardiac surgery practice were elaborated. Results: Principally, indications for an operative approach for heart insufficiency can be either symptomatic or from a prognostic perspective. Electrophysiological devices can prolong life by a prophylactic application and relieve symptoms of heart insufficiency by a rhythmological application. High-risk bypass operations, if necessary in combination with geometric ventricular corrective surgery can also prolong life and reduce the symptoms. Valvular diseases can be the cause and consequence of heart failure. Aortic valve replacement in high-grade diseases as well as mitral valve surgery for functional mitral valve insufficiency can be treated by guideline-conform surgery. In patients with end-stage heart failure heart transplantation or implantation of ventricular assist devices (VAD) can improve the quality of life and prolong life. Conclusion: Generally, patients with heart failure should always receive interdisciplinary treatment, if possible in centers which can provide specialized cardiac surgery.
CRIS-Team Scopus Importer:2024-06-04
Keywords: Cardiac resynchronization pacing therapy; Coronary artery bypass grafting; Heart failure; Heart transplantation; Implantable cardioverter-defibrillators; Ventricular assist device